Pengaruh Self Leadership, Komunikasi dan Kompetensi terhadap Kinerja Karyawan PT BPR Sangeh di Badung - Saputra, I Made Rai; Agustina, Made Dian Putri; Diputra, Gde Indra Surya (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study was to determine the effect of self-leadership, communication and competence partially and simultaneously on employee performance at PT. BPR Sangeh, Badung. Methods of data collection in this study by means of interviews, observation and questionnaires. Questionnaires were given to 34 respondents, to be further analyzed using multiple linear regression analysis, coefficient of determination, t-test and F-test. Based on the results of the analysis, it can be concluded that self-leadership has a positive and significant effect on employee performance at PT. BPR Sangeh, Badung. This means that the better the self-leadership, the better the performance of employees at PT. BPR Sangeh, Badung. Communication has a positive and significant effect on employee performance at PT. BPR Sangeh, Badung. This means that the better the implementation of communication, the higher the performance of employees at PT. BPR Sangeh, Badung. Competence has a positive and significant effect on employee performance at PT. BPR Sangeh, Badung. This means that the better the competence possessed by employees, the higher the performance of employees at PT. BPR Sangeh, Badung. Self leadership, communication and competence simultaneously have a positive and significant effect on employee performance at PT. BPR Sangeh, Badung.